SMART TOURISM AND SUSTAINABILITY: AN ANALYTICAL REVIEW OF ASIAN COUNTRIES - Dr. Dilli , Samadhi; Dr. K. Venkatalakshmi, Venkatalakshmi; Mr. Deepan, Deepan; Tursunqulov, Inom (Scientific practical conference, 2025)
The rapid emergence of the digital economy has transformed the tourism industry worldwide, with Asia leading as one of the fastest-growing regions for digital adoption. The proliferation of online booking platforms, mobile applications, digital payments, artificial intelligence, and social media marketing has reshaped how tourists plan, experience, and share their journeys. This study investigates the role of the digital economy in tourism development across Asian countries, highlighting both opportunities and challenges. Using secondary data from UNWTO, World Bank, and national tourism boards and the paper reveals that digital adoption has a significant positive impact on tourism growth. However, the study concludes that inclusive digital strategies, smart tourism policies, and sustainable practices are essential for ensuring that the digital economy continues to drive balanced tourism growth across Asia.